The postcranial anatomy of Coloradisaurus brevis (Dinosauria: Sauropodomorpha) from the Late Triassic of Argentina and its phylogenetic implications - Apaldetti, Graciela Cecilia (2013)
Basal sauropodomorphs from the Upper Triassic Los Colorados Formation of northwestern Argentina have been known for several decades but most of them are only briefly described. New postrcanial remains of Coloradisaurus brevis, the most gracile sauropodomorph from this unit, are described here and evaluated within a phylogenetic context. These materials belong to a single individual and include elements of the vertebral column, pectoral girdle, incomplete forelimb, pelvis, and hindlimb. These elements share autapomorphic features with the type specimen of Coloradisaurus brevis, and provide novel and unique features that diagnose this taxon, such as pubic apron with semicircular cross section and with a depression on its anterior surface, distal surface of the tibia deflected and facing posterodistally, and well-developed pyramidal dorsal process of the posteromedial corner of the astragalus. Several postcranial characters of Coloradisaurus are exclusively shared with Lufengosaurus, from the Lower Jurassic of China. The inclusion of this information in two recent phylogenetic datasets depicts Coloradisaurus as closely related to Lufengosaurus and well nested within Plateosauria. Both datasets used indicate strong character support for the inclusion of Coloradisaurus and Lufengosaurus within Massospondylidae.